A systematic review and meta-analysis on partial foot amputation in diabetic foot ulcers - Greenfield,S; Samarth,G; McGregor,A; Khan,M; Mohamed,A; Kanakala,S; Shalhoub,J (Journal of Vascular Surgery, 2026)
Objective:Partial foot amputations (PFA) serve as a limb-preserving alternative to major amputations in diabetic patients with advanced foot disease. This systematic review aimed to analyse clinical outcomes, including major and minor re-amputation rates, wound healing, re-ulceration, and mortality following PFA in diabetic adults.Data Sources and Review Methods:A comprehensive search of MEDLINE and Embase databases was conducted following PRISMA guidelines. Studies reporting on diabetic patients undergoing PFA for dysvascular or infective causes were selected. Out of 2437 screened abstracts, 46 studies met the inclusion criteria, representing 32,496 patients. Data extraction was performed using Covidence, and study quality was assessed using the ROBINS-I Tool.Results:Major amputation rates following PFA ranged from 0%-10% for digit and metatarsal amputations, 8%-54% for transmetatarsal amputation (TMA), and 11%-44% for midfoot amputations. The random effects model estimated a major amputation rate of 23% (95% CI 15%-30%), with high heterogeneity (I²=90%). Minor re-amputation rates varied from 12%-33%, notably high after 1st metatarsal amputation. One-year all-cause mortality was 16% (95% CI 10%-22%), with wide variability across studies. Delayed wound healing and high re-ulceration rates were common, particularly following TMA, with re-ulceration rates reaching up to 69%.Conclusion:PFA in diabetic patients carries significant risks of re-amputation, delayed healing, and limb loss. Clinicians should ensure that these risks are communicated during shared decision-making with patients. Standardisation of post-operative care, including multidisciplinary approaches involving orthotists and structured rehabilitation protocols, could help improve outcomes. Further research is needed to explore optimised care strategies and long-term functional outcomes following PFA.